Basic surgical instrumentation - Smith, Mary F.; Stehn, Joette L. (Philadelphia, Pennsylvania : W.B. Saunders Company, 1993)
A guide to basic surgical instruments used in a wide variety of procedures. A chapter on the basic care of instruments, sterilization and functions of instruments is followed by the core of the work which is organized by types of procedures, and shows the procedure set required for each.
Part 1 Introduction -- Part 2 Basic functions -- Part 3 Minor set -- Part 4 Major sets -- Part 5 Gynaecology -- Part 6 Rectal -- Part 6 Rectal -- Part 8 Plastic reconstructive -- Part 9 Ophthalmology -- Part 10 Ear, nose, throat -- Part 11 Endoscopy -- Part 12 paediatric -- Part 13 Orthopaedics -- Part 14 Thoracic -- Part 15 Cardiovascular -- Part 16 Neurosurgery -- Part 17 Laser
Includes index.
Keywords: SURGICAL EQUIPMENT